Phenotypic Analysis and Growth Performance of Rhode Island Red, Barred Plymouth Rock and their Hybrid at Jaba Mansehra, Pakistan: Phenotypic Analysis and Growth Performance of Rhode Island Red - Sifat Ullah,; Shumaila Noreen,; Muhammad Fiaz Khan,; Naqash Khalid,; Omer Dad,; Mohsin Ali, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Poultry farming is a big business in Pakistan. Poultry farming is a substantial supply of eggs and meat in rural areas, as well as a reliable source of income. Therefore the goal of this study is to compare the Rhode Island red, barred plymouth rock, and their hybrids’ phenotypic traits and egg-laying capacities. The 100-day-old Rhode Island Red, Barred Plymouth Rock, and cross chicks were used in the study at Jaba District Mansehra, KP, Pakistan. The whole flock was sheltered, fed, ventilated, and immunized. Breed 3 (Jabba 21) was reported to have the longest shanks (3.78 inches SL), followed by breed 1 (Rhode Island Red) and breed 2 (Barred Plymouth Rock) (3.47 inches SL). Breed 2 is the broadest shank at 0.47 SW, followed by Breed 1 at 0.43 SW and Breed 3 at 0.30 SW (0.43 Inches SW). The breadth of the shinbone did not change substantially from week 8 to week 13 (p=0.05), although body weight changed from week 1 to week 18. Breed 1 consumed the most feed (2,112 g), followed by Breed 3 (1,452 g) and Breed 2. (990 g). Breed 2 acquired the greatest amount of weight (1,638.57 g), followed by Breed 1 (1,557.07 g) and Breed 3. (1530.3 g). From the first to the eighteenth week of observations, there was a significant (p0.05) difference between the three chicken breeds in weekly body weight gain. Breeds 1, 2, and 3 saw growth rates of 1st 63.59, 2nd 64.02 and 3rd 64.03 percent. This research gave us a fresh perspective on several products that might come to market and contend with one another. This study provides insight into what will work best for Pakistan’s poultry sector going forward in the future.